Language and Power: A Critical Discourse Analysis of Egypt’s Housing Narratives - gamal, maram (AUC Knowledge Fountain, 2024)
The issue of housing in Egypt is an evolving historical phenomenon intricately tied to the Egyptian identity, and deeply embedded in the social and political fabric. Common language shapes actual realities and it forms an integral part of the cultural parameters. This research is a critical discourse analysis (CDA) of the housing narrative across four consecutive ruling regimes with distinct political orientations. It deploys a two-stage CDA approach. The first stage involves ideological codification of the narrative to chronologically organize them into their ideological orientations and categories. The second stage historicizes data via a dual approach, namely integrating Norman Fairclough's three-dimensional model and Michel Foucault's power-oriented discourse analysis. Through examining newspaper archives, media outlets, policy statements, legal documents, and public announcements, the study aims to unveil the ideologies embedded in the social, political, and economic fabric and the relationship to the language used in the narrative and the actual situation. CDA deploys linguistic tools to explore the evolution of the narrative by investigating lexical changes, the use of assumptions, and the dialogical orientations in the data collected, elucidating the profound impact of language on shaping, and reinforcing the housing industry in Egypt. It is argued that the discourse surrounding the housing industry in Egypt unfolds as a dynamic narrative, marked by fluctuations in the identification of a ‘crisis’ and the perceived causes behind it. Hence, the term ‘housing crisis’ has emerged as a metaphor in the housing narrative across the time frames under study. This research discerns the intricate relationship between the identified categories in the housing narrative and how they evolve over time and the role of power in constructing actual housing situation. Ultimately, through the application of CDA, it becomes clear that the ‘crisis’ narrative serves as a political construct to establish power and control.